Vegetation Potential Analysis In Lake Mooat Tourist Area, North Sulawesi - REMPAS, Robby D.J.; PASAMBUNA, Hendratno (Journal of Tourism Economics and Policy, 2023)
This study aimed to assess the potential vegetation of trees in the Lake Mooat tourist area and identify the dominant tree species in this attraction. The research employed a descriptive quantitative approach and was conducted in October-November 2018. The study area featured a plateau topography at an approximate elevation of 1,090 meters above sea level, as indicated in the Lake Mooat Potential Study Report 2013. The survey method was used, and plots were established with dimensions of 20 meters by 20 meters. Data collected included tree density, relative density, frequency, relative frequency, dominance, and the Important Value Index (INP). The findings revealed the presence of 242 individual trees and identified 15 tree species. Among these species, Mahogany had the highest Important Value Index, reaching 156.29%, indicating its ecological significance in the area. Mahogany also emerged as the most dominant tree species at the Lake Mooat tourist attraction, with a dominance value of 55.51%. In conclusion, the study highlighted the rich diversity of tree vegetation in the Lake Mooat tourist area, with Mahogany as the most significant and dominant species. On the other hand, the tree species with the lowest Important Value Index was Trembesi (Albizia saman), registering a value of 1.563%. These findings contribute to understanding the ecological composition and potential conservation efforts for the vegetation in this region.